The effect of self‐generated versus externally generated actions on timing, duration, and amplitude of blood oxygen level dependent response for visual feedback processing. Issue 16 (2nd September 2022) - Kavroulakis, Eleftherios; van Kemenade, Bianca M.; Arikan, Belkis Ezgi; Kircher, Tilo; Straube, Benjamin
Abstract: It has been widely assumed that internal forward models use efference copies to create predictions about the sensory consequences of our own actions. While these predictions have frequently been associated with a reduced blood oxygen level dependent (BOLD) response in sensory cortices, the timing and duration of the hemodynamic response for the processing of video feedback of self‐generated (active) versus externally generated (passive) movements is poorly understood. In the present study, we tested the hypothesis that predictive mechanisms for self‐generated actions lead to early and shorter neural processing compared with externally generated movements. We investigated active and passive movements using a custom‐made fMRI‐compatible movement device. Visual video feedback of the active and passive movements was presented in real time or with variable delays. Participants had to judge whether the feedback was delayed. Timing and duration of BOLD impulse response was calculated using a first (temporal derivative [TD]) and second‐order (dispersion derivative [DD]) Taylor approximation. Our reanalysis confirmed our previous finding of reduced BOLD response for active compared to passive movements. Moreover, we found positive effects of the TD and DD in the supplementary motor area, cerebellum, visual cortices, and subcortical structures, indicating earlier and shorter hemodynamic responses for active compared to passive movements. Furthermore, earlier activation in the putamen for active compared to passive conditions was associated with reduced delay detection performance. These findings indicate that efference copy‐based predictive mechanisms enable earlier processing of action feedback, which might have reduced the ability to detect short delays between action and feedback. Abstract : Internal forward models use efference copies to create predictions about the sensory consequences of our own actions. Consideration of timing and duration in addition to amplitude of the blood oxygen level dependent response, is important to predict and understand human behavior. Efference copy‐based predictive mechanisms enable earlier and shorter processing of action feedback, which reduced the ability to detect short delays between action and feedback.